2004
DOI: 10.1016/j.ejcts.2004.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection by remote preconditioning: the role of nuclear factor kappa-B p105 and inducible nitric oxide synthase

Abstract: Delayed cardioprotection induced by hind limb preconditioning involves signaling through NFkappaB and iNOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 22 publications
5
43
0
2
Order By: Relevance
“…The protective effect of limb RIPC on the cardiovascular system has been shown previously 8 , and a role for adenosine 21 and nitric oxide 22 has been postulated. The underlying mechanism and pathways, whether humoral or neurogenic or both, remain unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The protective effect of limb RIPC on the cardiovascular system has been shown previously 8 , and a role for adenosine 21 and nitric oxide 22 has been postulated. The underlying mechanism and pathways, whether humoral or neurogenic or both, remain unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Nitric oxide has an important role in delayed remote cardioprotection 22 and in the early protection of adipocutaneous flaps with limb RIPC 11 . The role of nitric oxide in early remote cardioprotection is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have studied the role of NF-jB activation during sepsis, leading to the suggestion that NFjB activation is an early step in the pathogenesis of sepsisinduced organ injury [20,21]. A dual role for NF-jB was demonstrated in the heart by Li et al [19]; although excessive NF-jB activation in I/R injury had harmful effects, activation of NF-jB following limb preconditioning led to an adaptive response following sustained I/R injury. In their study, preconditioning of the hind limbs caused activation of NF-jB in both the I/R hind limbs and in the heart.…”
Section: Discussionmentioning
confidence: 97%
“…In a mouse model, Li et al [19] demonstrated that RIPC significantly reduces the myocardial infarct size by stimulating the expression of NF-jB proteins in both limb skeletal muscle and myocardium. These authors also suggested that this mechanism may also induce protective signals in the limb that are then transferred to the heart, leading to ischemic adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…PRIT was initiated one week after the first MI. PRIT stimulation was performed using an external tourniquet that was bilaterally applied around the upper hind limb joint for 5 min, followed by 5-min reperfusion for a total of 6 cycles, once daily for five days a week [13]. Circulatory arrest in the limb was confirmed by vascular Doppler ultrasound [14].…”
Section: Induction Of Physiologic Remote Ischemic Training (Prit)mentioning
confidence: 99%